PERMAINAN KERJASAMA UNTUK MENINGKATKAN KECERDASAN EMOSI SISWA - Martini, Entin; Mardiyati, Siti; Wagimin, Wagimin (Universitas Sebelas Maret, 2014)
This research aimed to determine effectiveness of the implementation of the cooperation game techniques in group counseling to improve students?emotional intelegent. This research was conducted on the basis that in Junior High School in Karanganyar. This research was quasy-experimental design. The subjects were students who have low emotional intelligence, ie students who earn below the mean pretest scores. Analysis using t-test statistical formula. The analysis showed a p values 0.000, which means that there is a difference between the experimental group who had been given a treatment with a control group who did not receive treatments. It shows that the game under the guidance of the group effective cooperation to improve the emotional intelligence of students.